The decade-long growth of government-authored news media in China under Xi Jinping - Hannah Waight; Yin Yuan; Margaret E. Roberts; Brandon M. Stewart (Proceedings of the National Academy of Sciences, 2025)
Autocratic governments around the world use clandestine propaganda campaigns to influence the media. We document a decade-long trend in China toward the planting of government-authored articles in party and commercial newspapers. To examine this phenomenon, we develop an approach to identifying scripted propaganda—the coerced reprinting of lightly adapted government-authored articles in newspapers—that leverages the footprints left by the government when making media interventions. We show that in China, scripted propaganda is a daily phenomenon—on 90% of days from 2012 to 2022, the vast majority of party newspapers include at least some scripted propaganda at the direction of a central directive. On particular sensitive days, the amount of scripted propaganda can spike to 30% of the articles appearing in major newspapers. We show that scripted propaganda has strengthened under President Xi Jinping. In the last decade, the front page of party newspapers has evolved from 5% scripted articles to approximately 20% scripted. This government-authored content throughout the paper is increasingly homogeneous—fewer and fewer adaptations are done by individual newspapers. In contrast to popular speculation, we show that scripted content is not only on ideological topics (although it is increasingly ideological) and is also very prevalent in commercial papers. Using a case study of domestic coverage of COVID-19, we demonstrate how the regime uses scripting to shape, constrain, and delay information during crises. Our findings reveal the wide-ranging influence of government-authored propaganda in China’s media ecosystem.